Awareness and Use of mHealth Apps: A Study from England - Reem Kayyali; Aliki Peletidi; Muhammad Ismail; Zahra Hashim; Pedro Bandeira; Jennifer Bonnah (MDPI AG, 2017)
Purpose: Mobile health (mHealth) solutions have become an inevitable element of the healthcare landscape. The recommendation and use of mHealth is important, but it is often underutilised. This study was conducted in England. It aimed to determine the use and recommendation of mHealth apps by pharmacists, the public's perceptions of mHealth apps in general, and the awareness and use of health apps by diabetic patients in particular. Methods: The study used a mixed research approach, utilising a sequence of survey-based questionnaires with pharmacists and the general public, followed by semi-structured interviews with diabetic patients. Results: Pharmacists' questionnaires revealed that 56% of the respondents were aware of health apps, 60% of which recommended them to patients. Over 76% of the individuals owned a smartphone. The types of applications that saw the most use from the general public were health and lifestyle apps (24%), social apps (19%), followed by news (18%). Although eight out of nine diabetic patients owned a smartphone, only three used diabetes apps. Diabetic patients also suggested an interest in using diabetes apps to aid in optimising care via the utilisation of visual aids, reminders, recording patient data, social coaching, and remote collaboration with healthcare professionals (HCPs), but time was seen as the biggest obstacle to using a diabetes mHealth application. Conclusion: Despite the growing number of mHealth apps, the level of awareness and usability of such apps by patients and pharmacists was still relatively low. Nevertheless, the majority who used health apps found them to be beneficial, and the public agreed that it helped them to live a healthier lifestyle. Therefore, health apps have great potential in health promotion. Pharmacists are ideally placed to promote them and make patients more aware of them. To increase the use of these apps, it is necessary to first increase awareness and knowledge of these apps, both to the public and to healthcare professionals.